AUTHOR'S PSYCHOLOGICAL METHOD OF DIAGNOSING EMOTIONAL INDICATORS OF GIRLFRIENDS (Psychology Travelogs, 2025)
The article reveals the process and results of the development and testing of the author's psychological methodology «Diagnosis of Emotional Indifference Between Spouses" (DEBP). The essence of the concept of "indifferent marriage partner (partner)» is clarified as someone who does not pay attention, does not show affection for his/her wife (husband). It is noted that a prolonged lack of attention, sensitivity, and responsiveness between spouses generates a crisis of emotional indifference and can lead to divorce. Signs of a crisis of emotional indifference between partners are identified: the disappearance of romantic moods; increasing differences in views and tension in relationships (conflicts, quarrels); increased manifestations of negative emotions and negative states (aggression, apathy, asthenia); manifestations of intimate and sexual indifference (decreased desires, passions); the emergence of a feeling of disappointment (doubts about the correctness of the choice of a marriage partner). The goal of the psychological method of DEBP is to identify a prolonged lack of satisfaction with the marital partnership, which generates a family crisis of emotional indifference. DEBP allows spouses to realize the presence of a family crisis in their lives, which generates disappointment in the marital partner and disharmony in family life.Based on the content characteristics of the emotional indifference of spouses and its signs, test statements were constructed. According to the results of the structural analysis of the emotional indifference of marriage partners, the statements of the questionnaire reflect 6 scales: desire to worry about the partner; admiration for the partner; interest, attention to the partner; intimate and sexual indifference; negative emotions and negative states; doubt in choosing a partner. The advantage of this scale is the accuracy of measurement and the ability to analyze data using parametric and non-parametric criteria.
Keywords: emotional indifference of spouses; crisis; diagnostics; psychological methodology